Lake Sentani Water Quality Index based on NSF-WQI as Raw Water for Drinking Water for Lake Sentani Coastal communities, Jayapura Regency - Bambang Suhartawan; Jusuf Haurissa; Sarah Agustina Rumawak (Ridwan Institute, 2022)
Lake Sentani has an area of ​​about 9,630 ha and is located at an altitude of 72 m above sea level. Residents who live on the shores and shores of the lake, use the lake water for bathing, washing and latrine purposes. They also use it as raw water for drinking water and also as a means of transportation and even throw household waste into the lake water. There are 5 (five) rivers as the inlet, namely the Hawaii, Yamolo, Klandeli, Dofroko and Hobay rivers and there is one estuary, the Djaifuri River which is located in the east (Puay area). This study aims to determine the index of each water quality parameter and the total index of water quality. The water quality index parameters studied were; DO, Fecal coliform, pH, BOD, Temperature, Total Sulfate, Nitrate-N, Turbidity and Total Dissolved Solid (TDS). Sampling was carried out at 3 (three) sample points (stations) namely the mouth of the Haway River (Ifale Sentani), the middle of the lake (Ayapo Sentani) and the Upper Jaifuri River (Puay Yoka). Determination of the Total Water Quality Index is calculated using the National Sanitation Foundation's Water Quality Index (NSF-WQI) method for both Lake Sentani water and the total standard water quality index. The test results of each parameter are compared with the Class 1 Water Quality Standards Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. The results obtained from the research at 3 (three) research stations turned out that station 1 obtained an index of 44.24 and station 3 obtained an index of 46.60 both classified as Bad (bad), station 2 obtained an index of 51.42 classified as Medium (medium), while the standard water quality class 1 obtained a quality index of 47.24 classified as Bad (poor) too. Thus, when compared with the standard water quality index of class 1, what meets the requirements as raw water for drinking water is lake water at station 2 (Ayapu Sentani) where the index value is greater than the quality standard.